Programa de equoterapia: intervenção com um praticante com deficiência visual - Silva, Fernanda Carolina Toledo da [UNESP]; Nabeiro, Marli [UNESP] (My University, 2012)
The hippotherapy is a therapeutic and educational method that uses the horse within an interdisciplinary approach in the areas of health, education and riding, seeking the biopsychosocial development of people with disabilities and/or special needs. The method generates the practitioner positive effects, such as physical, social and psychological benefits. The goal of this study was to investigate alterations with a practitioner with visual impairment during their participation in a hippotherapy program. The study is characterized by a qualitative and descriptive research, in the form of case study. Data were collected through interviews with the mother of the practitioner and filming, photographs and systematic observation of the sessions. Improvements were found in the behavior of practicing at home, and there was progress in motor performance, and self-confidence generated by the domain horse. It is concluded that the hippotherapy program generated physical, psychological and social benefits to the practitioner.

A equoterapia é um método terapêutico e educacional que utiliza o cavalo dentro de uma abordagem interdisciplinar, nas áreas de saúde, educação e equitação, buscando o desenvolvimento biopsicossocial de pessoas com deficiência e/ou com necessidades especiais. O método gera efeitos positivos ao praticante, como benefícios físicos, sociais e psicológicos. O objetivo deste estudo foi verificar alterações ocorridas com um praticante com deficiência visual durante sua participação em um Programa de Equoterapia. O trabalho caracteriza-se por uma pesquisa qualitativa e descritiva, na forma de estudo de caso. Os dados foram coletados por meio de entrevista com a mãe do praticante e filmagens, fotografias e observação sistemática das sessões. Foram encontradas melhoras no comportamento do praticante em casa, e houve progresso no desempenho motor, além da autoconfiança gerada pelo domínio do cavalo. Conclui-se que o Programa de Equoterapia gerou benefícios físicos, psicológicos e sociais no praticante.
Hippotherpy program: intervention with a practitioner with visual impairment
Keywords: Hipptherapy; Visual impairment; Physical activity; Equoterapia; Deficiência visual; Atividade motora